The Whole Picture of Female Nurse Faculty Leaders: A Systematic Review of Qualitative Studies - Suarilah, Ira; Aurizki, Gading Ekapuja; Purwaningsih, Purwaningsih; Mulyadi, Mulyadi; Vourvachi, Christina (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: Gender stereotypes influence women and men who work as nurses. In education setting, the dominance of female nurses has been challenging given their respective roles in management and leadership, both professionally and personally.Objective: To explore the experience and synthesise available literature on female nurse leaders in the academic settings.Methods: Systematic review of qualitative study on any type of qualitative from academic database: ProQuest, PubMed, CINAHL, and MEDLINE was conducted. Starting from 1st January 1990 to 31 December 2021. The criteria; freely accessible, complete in terms of content, authored, published in the English language, and combination of keywords including nurse, nursing, faculty, dean, head, and director were applied. The review was reported following PRISMA format. The studies included were assessed using the Critical Appraisal Skills Program tool (CASP) 2017.Results: The screening process resulted in the selection of fourteen (14) studies from the USA, Canada, UK, and Australia that used a range of qualitative methodologies, including descriptive explorative, phenomenology, grounded theory, feminist research, case studies, and a number of data collection techniques, including open-surveys, interviews, field notes, campus observations, document analysis, and analytic memos. Thematic analyses were applied and yielded six main themes: dealing with power imbalance and gender discrimination; addressing problems related to people; disruption in fulfilling leadership roles; leadership personalities; people-oriented leadership quality; and change-oriented leadership quality.Conclusion: Female faculty leaders in nursing reported a variety of personal and professional challenges. The existing literature scarcely captured the gender-specific challenges encountered, including gender stereotyping, and struggle to balance their personal and professional life. Therefore, it is crucial that nurses provide chances for the following leaders in order to enhance nursing education, support the process of leadership regeneration, and develop the profession.